Kinerja Gabungan Kelompok Tani Kasus: Kabupaten Lampung Selatan Provinsi Lampung - Fauziah Y. Adriyani; Aida Vitayala S Hubeis; Richard W.E Lumintang (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2011)
The objectives of this research were to identify the internal and external factors related to Gapoktan performance and also to analyst the relation among the internal and external factors. The research conducted in March-May 2010 in South Lampung regency Lampung Province, the data were collected by interview technique using questionners to key persons. A number of 184 farmer groups respondents participated were randomized sampling from 20 sample of Gapoktan. Descriptive statistic and rank Spearman Correlation Test from SPSS 17.00 were used to analize the data. The result showed that internal factors such as farmer group activity, farmer group cohessivity, interaction among farmer group, the structure of Gapoktan’s organization, and leadership had positive and significant correlation with Gapoktan performance. While the position of farmer group, farmer group participation, and desicion making process had non significant correlation with Gapoktan performance. The external factors such as goverment policy, relationship with the other institution, capital loan, and extension intensity had positive and significant correlation with Gapoktan performance. Meanwhile, the change agent (PPL) performance had non significant correlation with Gapoktan performance. Most of variable both internal and external factors had a positive and significant relation to each others.Keywords: performance, associatian of farmer group, Gapoktan